2002
DOI: 10.1046/j.1365-294x.2002.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness and female spatial organization in a solitary carnivore, the raccoon, Procyon lotor

Abstract: Among mammals, some of the most common types of cohesive social groupings originate from natal philopatry through the extended mother family. This retention of females within social groups (i.e. the nonrandom dispersion of female relatives in space) should affect population genetic structure. We examined the relationship between genetic relatedness and female spatial organization in a wild population of the North-American raccoon, Procyon lotor, a solitary carnivore in east Tennessee. Multilocus genetic band-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 53 publications
7
56
2
Order By: Relevance
“…For raccoons (Procyon lotor), Ratnayeke et al (2002) confirmed the corollary expectation that local females are genetically more similar than males. If females remain close to their natal site (i.e.…”
Section: Introductionsupporting
confidence: 57%
“…For raccoons (Procyon lotor), Ratnayeke et al (2002) confirmed the corollary expectation that local females are genetically more similar than males. If females remain close to their natal site (i.e.…”
Section: Introductionsupporting
confidence: 57%
“…Average gene diversity across all loci (Nei, 1987) within Table 2. Analysis of molecular variance (AMOVA) for individuals from Emas National Park and Pantanal using Nei and Li (1979) (Cooper, 2000), carnivores (Ratnayeke et al, 2002), and primates (Neveu et al, 1998). Few studies using the RAPD technique have been reported on cervid species.…”
Section: Resultsmentioning
confidence: 99%
“…Their study revealed that local populations sorted into two distinct groups, exhibiting either significantly greater or lesser (non-significant) levels of kin-structure than would be expected at random, a pattern primarily driven by the fact that contributions to population persistence stemming from immigration versus natality differed markedly among local populations. This finding, in combination with strong evidence for a high degree of site fidelity of female raccoons to their natal patch (Gehrt and Fritzell 1998, Ratnayeke et al 2002, Cullingham et al 2008, Dharmarajan et a. 2009, Beasley et al 2013, led (Dharmarajan et al 2014) to hypothesize that significant spatial variation in vital rates exists for raccoons inhabiting fragmented agricultural ecosystems, consistent with expectations of a sourcesink population structure.…”
Section: Introductionmentioning
confidence: 78%
“…However, we believe apparent survival of adult female raccoons closely resembles true survival in our study area. Dispersal in raccoons is male-biased (Ratnayeke et al 2002, Cullingham et al 2008, Dharmarajan et al 2009) and predominantly occurs between 0.5 and 1.5 years of age (Gehrt 2003). Moreover, adult females maintain small home ranges within our study area (58 ha) and no permanent emigration was observed among 37 females tracked using radiotelemetry during previous research conducted within our study landscape (maximum home range size was 160 ha; Beasley et al 2007.…”
Section: Population Growth Ratementioning
confidence: 99%